1979
DOI: 10.1126/science.760200
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic Factor-Induced Release of Membrane Calcium in Rabbit Neutrophils

Abstract: The interaction of chemotactic factors (fMet-Leu-Phe and C5a) with rabbit neutrophils leads to rapid and specific release of membrane calcium, as evidenced by changes in the fluorescence of cell-associated chlorotetracycline. These two structurally different stimuli appear to interact with the same pool of membrane calcium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

1979
1979
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(38 citation statements)
references
References 16 publications
1
36
1
Order By: Relevance
“…Under the conditions in Table III, BOC-Phe-Leu-Phe-LeuPhe alone did not affect PMN migration to zymosan-activated serum (see Table III), whereas the PMN chemotactic response to FMLP was significantly decreased (see Table III). The findings using BOC-Phe-Leu-Phe-Leu-Phe suggest that mitochondrial PMN chemoattractants interact with neutrophil N-formylmethionyl peptide receptors (2,17,30) and imply that the chemotactic activity of disrupted mitochondria and purified mitochondrial proteins is mediated, at least in part, through N-formylmethionine residues present in these proteins. * Concentrations: CYOX, 10 6 M; CYOX subunit I (CYOXI), 10-" M; CYOX subunit lI (CYOXn), 10 -~ M; activated (zymosan) human serum, 10% (vol/vol); FMLP, 10 -s M; HeLa WI-38, and foreskin fibroblast mitochondria, 100 ~g (protein).…”
Section: Inhibition Of Mitochondrial Chemotactic Activity By Boc-phe-mentioning
confidence: 99%
See 1 more Smart Citation
“…Under the conditions in Table III, BOC-Phe-Leu-Phe-LeuPhe alone did not affect PMN migration to zymosan-activated serum (see Table III), whereas the PMN chemotactic response to FMLP was significantly decreased (see Table III). The findings using BOC-Phe-Leu-Phe-Leu-Phe suggest that mitochondrial PMN chemoattractants interact with neutrophil N-formylmethionyl peptide receptors (2,17,30) and imply that the chemotactic activity of disrupted mitochondria and purified mitochondrial proteins is mediated, at least in part, through N-formylmethionine residues present in these proteins. * Concentrations: CYOX, 10 6 M; CYOX subunit I (CYOXI), 10-" M; CYOX subunit lI (CYOXn), 10 -~ M; activated (zymosan) human serum, 10% (vol/vol); FMLP, 10 -s M; HeLa WI-38, and foreskin fibroblast mitochondria, 100 ~g (protein).…”
Section: Inhibition Of Mitochondrial Chemotactic Activity By Boc-phe-mentioning
confidence: 99%
“…We further tested the notion that the PMN chemotactic activity of mitochondrially synthesized proteins is mediated through the presence of an N-formylmethionine residue by using the formyl peptide antagonist BOC-Phe-Leu-Phe-Leu-Phe (17,30). BOC-PheLeu-Phe-Leu-Phe is thought to inhibit the PMN response to N-formylmethionine containing peptides by competitively inhibiting the binding of these factors to specific cell surface receptors (2,17,30). As shown in Table III, when BOC-Phe-Leu-PheLeu-Phe was present in both compartments of the chemotaxis chamber, the PMN chemotactic response to purified mitochondrial proteins or disrupted mitochondria was significantly reduced.…”
Section: Inhibition Of Mitochondrial Chemotactic Activity By Boc-phe-mentioning
confidence: 99%
“…In stimulated cells, there was less extramitochondrial fluorescence. Naccache et al (45) have recently reported that chemotactic factors induce release of membrane calcium in rabbit neutrophils; these authors also used the fluorescence of CTC-treated cell suspensions to measure membrane-bound calcium, and Taljedal (64) described methodology for microfluorimetric measurement of CTC. Since the fluorescence signal of interest, when CTC is used as a probe, comes entirely from the cells, one would expect that this procedure could be adapted almost unchanged for flow cytometry.…”
Section: Tetracyclines As Probes For Membrane-bound Calciummentioning
confidence: 99%
“…fMLP, PAF and C5a (Naccache et al, 1979;Clancy et al, 1983;Naccache et al, 1986). These compounds bind to specific cell-surface receptors to stimulate the phospholipase C-dependent release of diacylglycerol and inositol trisphosphate, a process mediated by pertussis toxinsensitive, guanine nucleotide-binding proteins (G proteins) (Becker et al, 1985;Naccache et al, 1986;Shirato et al, 1988).…”
Section: Introductionmentioning
confidence: 99%